2017
DOI: 10.1177/1934578x1701200847
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyllum pinnatum – Reverse Engineering of an Anthroposophic Herbal Medicine

Abstract: Bryophyllum pinnatum (syn. Kalanchoe pinnata), a plant native to Madagascar, was introduced into anthroposophic medicine in the early 20 th century. In recent years, a number of investigations were conducted on the chemical composition, pharmacological properties, and clinical efficacy of Bryophyllum. Here the phytochemistry, and pharmacological and clinical data are reviewed. With respect to pharmacology, a special focus was put on properties related to the use in anthroposophic medicine as a treatment for "h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…; family Crassulaceae] is a perennial succulent plant that grows widely in tropical and subtropical areas. In Europe, B. pinnatum started to be used in anthroposophic medicine [14] as treatment of preterm labour [15, 16]. Retrospective analyses of the clinical practice revealed good efficacy of B. pinnatum preparations in this indication [15, 16], which was corroborated by a matched pair study [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…; family Crassulaceae] is a perennial succulent plant that grows widely in tropical and subtropical areas. In Europe, B. pinnatum started to be used in anthroposophic medicine [14] as treatment of preterm labour [15, 16]. Retrospective analyses of the clinical practice revealed good efficacy of B. pinnatum preparations in this indication [15, 16], which was corroborated by a matched pair study [17].…”
Section: Introductionmentioning
confidence: 94%
“…In Europe, B. pinnatum started to be used in anthroposophic medicine [14] as treatment of preterm labour [15, 16]. Retrospective analyses of the clinical practice revealed good efficacy of B. pinnatum preparations in this indication [15, 16], which was corroborated by a matched pair study [17]. Results of a prospective randomised trial on acute tocolysis are in line with good efficacy, but have to be interpreted with caution since - due to poor recruitment rate - the study was discontinued before completion [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, BP started to be used at the beginning of the 20th century in anthroposophic medicine, a form of holistic medicine with an integrative approach . The indications for which BP is often used within this type of medicine and more recently also in conventional settings include preterm labor, overactive bladder, and sleep disorders . Several retrospective and a few prospective studies on the treatment of preterm contractions and of overactive bladder with BP preparations have been performed and suggest good effectiveness and very good safety/tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Preparations of Bryophyllum pinnatum (BP) leaves have been proposed to possess both sedative and muscle relaxant properties . Moreover, prospective observational trials performed with pregnant women and cancer patients revealed good effectiveness in the treatment of sleep disorders with BP 50% chewable tablets (each 350 mg tablet corresponds to 170 mg of leave press juice, dried down to 17 mg by mixing with lactose; 100 mg dried BP matter in 1 g).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the use of remedies prepared from B. pinnatum leaves was limited for a long time to anthroposophic medicine. Initially, they were used for the treatment of various hyperactivity disorders [3,4], and only in the 1970s was B. pinnatum introduced by the German gynaecologist Werner Hassauer (1928Hassauer ( -1993 as a routine treatment of preterm labour [5]. In Switzerland, B. pinnatum is used in gynaecology and obstetrics against premature contractions, restlessness, and overactive bladder [6].…”
Section: Introductionmentioning
confidence: 99%